Identification of Senescence-Related Subtypes, the Development of a Prognosis Model, and Characterization of Immune Infiltration and Gut Microbiota in Colorectal Cancer - Dai, Ju-Ji; Fu, Yang-Yang; Zhong, Xi-Qiang; Cen, Wei; Ye, Mao-Fei; Chen, Xi-Han; Pan, Yi-Fei; Ye, Le-Chi (Frontiers in Medicine, 2022)
Although cellular senescence is associated with tumorigenesis, the subtype and prognostic signatures of senescence-related genes (SRGs) in the tumor microenvironment (TME) and gut microbiota have not been determined. Analysis of 91 SRGs obtained from the GSEA and MSigDB, and mRNA sequencing of genes in the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases enabled the identification of two distinct molecular types of colorectal cancer (CRC). Patient samples were clustered into two subtypes, with Kaplan-Meier survival analyses showing significant differences in patient survival between the two subtypes. Cluster C2 was associated with patient clinicopathological features, high immune score, high abundance of immune infiltrating cells and somewhat high abundance of bacteria. A risk model based on eight SRGs showed that a low risk score was characterized by inhibition of immune activity and was indicative of better prognosis in patients with CRC. In combination with clinical characteristics, risk score was found to be an independent prognostic predictor of survival in patients with CRC. In conclusion, the present study showed that senescence-related subtypes and a signature consisting of eight SRGs were associated with CRC patient prognosis, as well as with immune cell infiltration and gut microbiota. These findings may enable better prediction of CRC patient prognosis and facilitate individualized treatments.